Innate Immune Antagonism of Mosquito-Borne Flaviviruses in Humans and Mosquitoes - Ahmed M. E. Elrefaey (MDPI AG, 2021)
Mosquito-borne viruses of the Flavivirus genus (Flaviviridae family) pose an ongoing threat to global public health. For example, dengue, Japanese encephalitis, West Nile, yellow fever, and Zika viruses are transmitted by infected mosquitoes and cause severe and fatal diseases in humans. The means by which mosquito-borne flaviviruses establish persistent infection in mosquitoes and cause disease in humans are complex and depend upon a myriad of virus-host interactions, such as those of the innate immune system, which are the main focus of our review. This review also covers the different strategies utilized by mosquito-borne flaviviruses to antagonize the innate immune response in humans and mosquitoes. Given the lack of antiviral therapeutics for mosquito-borne flaviviruses, improving our understanding of these virus-immune interactions could lead to new antiviral therapies and strategies for developing refractory vectors incapable of transmitting these viruses, and can also provide insights into determinants of viral tropism that influence virus emergence into new species.